Loanword Adaptation in Indonesian through Podcasts: : Semantic and Phonological Perspectives - Najim Sajidah Putri (Language Horizon: Journal of Language Studies, 2025)
This study examines the phonological and semantic changes of English loanwords used in the podcast Nebeng Boy: A New Era (2024). The focus is on how these borrowed words are adapted into Indonesian both phonetically and semantically. Drawing on Schane’s (1973) framework of phonological change, the loanwords undergo processes such as assimilation, syllable structure modification (epenthesis and elision), neutralization, and weakening/strengthening. These adaptations reflect the phonological adjustments required to fit the simpler Indonesian sound system. Semantically, the analysis follows Bloomfield’s (1933) classification of meaning change, including narrowing, broadening, metaphor, metonymy, amelioration, and pejoration. The findings show that most of the loanwords experience narrowing or broadening, influenced by digital culture, social media, and informal usage. No cases of pejoration were identified. This study highlights how digital media, particularly podcasts, serve as dynamic platforms for linguistic change, where foreign vocabulary is not only adopted but also reshaped to meet the local communicative and cultural needs.